Assessment of DNA damage in a group of professional dancers during a 10-month dancing season. Issue 13 (3rd August 2017) - Esteves, Filipa; Teixeira, Eduardo; Amorim, Tânia; Costa, Carla; Pereira, Cristiana; Fraga, Sónia; De Andrade, Vanessa Moraes; Teixeira, João Paulo; Costa, Solange
ABSTRACT: Despite the numerous health benefits of physical activity, some studies reported that increased intensity and duration may induce oxidative stress in several cellular components including DNA. The aim of this study was to assess the level of basal DNA damage as well as oxidative DNA damage in a group of professional dancers before and after a 10-month dancing season. A group of individuals from general population was also assessed as a control. The alkaline version of the comet assay was the method selected to measure both basal DNA damage and oxidative stress, since this method quantifies both endpoints. In order to measure oxidative stress, the comet assay was coupled with a lesion-specific endonuclease (formamidopyrimidine glycosylase) to detect oxidized purines. The levels of oxidative DNA damage in dancers were significantly increased after the dancing season. Pre-season levels of oxidative DNA damage were lower in dancers than those obtained from the general population, suggesting an adaptation of antioxidant system in dancers. Results of the present biomonitoring study indicate the need for more effective measures to protect ballet dancers from potentially occupational health risks related to regular intensive physical exercise.